Optimising the public transport priority at road intersections. Issue 8 (6th July 2018) - De Keyser, Olivier; Hillewaere, Menno; Audenaert, Pieter; Maenhout, Broos
Abstract : A lot of effort is put into improving the efficiency of transportation and the optimisation of the current traffic situations. Nevertheless, this will not be sufficient to deal with the increasing number of road users. Public transportation is an appealing economical solution, although its quality is dependent on the efficiency of traffic lights and congestions. The aim of this study is to investigate the impact of public transport (PT) priority on the performance of a single road intersection with two two‐way crossing streets and a dedicated tram line. In this perspective, the authors set up a microscopic simulation experiment to evaluate different PT priorities. The study is applied to a road intersection in Ghent (Belgium) and all relevant inputs are based on real‐life data. Overall, the total travel time of all actors advocate for traffic light control regulations that accommodate regular road users at the expense of PT and contradict the current priority settings of the signal control system. However, the passenger‐dependent travel times give a slightly nuanced view advocating a delayed priority or even no priority for PT vehicles only during the evening peak.